A Novel Decoding Algorithm for BICM-ID Embedded Turbo Codes - Jian Wang; Jianping Li; Chaoshi Cai (Institute of Advanced Engineering and Science, 2014)
Bit-interleaved coded modulation iterative decoding (BICM-ID) embedded turbo code is widely used in wireless communication because of its excellent performance. This paper proposes an improved logarithmic maximum a posteriori (Log-MAP) algorithm for BICM-ID embedded turbo codes. It can yield excellent bit error rate (BER) performance with much lower complexity. The proposed algorithm exploits a linear interpolation and Least Squares approximation function to replace the logarithmic correction in the Jacobian logarithmic function, which avoids complicated logarithm look-up table operations in Log-MAP algorithm. Simulation results show that the novel algorithm can offer almost equivalent performance to the optimal algorithm with much less computation. Compared with the improved MAX-Log-MAP algorithm proposed by Talakoub, the proposed algorithm can reduce about 36% of computational complexity, meanwhile it achieves 0.1db-0.16db performance gains. In addition, it obtains 0.35-0.4db gains than MAX-Log-MAP algorithm. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4596